How important is cultural background for the level of intergenerational mobility? - Daniel D. Schnitzlein (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2011)
Using results on brother correlations of different groups of second generation immigrants based on administrative data from Denmark, this note analyzes the role of cultural background in the determination of the level of intergenerational mobility. The estimated correlations indicate that cultural background is not an important factor for the level of intergenerational mobility.
Keywords: J62; 330; Intergenerational mobility; Sibling correlations